MEMBACA NARASI NAZAR YEFTA DARI CARA PANDANG KAUM PENTAKOSTAL - Manurung, Kosma (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2023)
A father must educate, protect, nurture, provide a sense of security and comfort to his children. However, what the Bible says regarding the narrative of Jephthah's vows does not indicate such a thing. Because of the impact of this vow, Jephthah finally had to offer his only daughter as a burnt offering to God. In fact, God, as explained in the Bible, never wanted his burnt offering to be a human. This article attempts to read the narrative of Jephthah's vows from a Pentecostal perspective. It is hoped that the use of qualitative narrative methods and elaborating them with literature studies will provide an in-depth insight into Jephthah's life, providing a strong picture regarding the narrative of Jephthah's vow in Judges 11: 29-40, and the way Pentecostals view this vow. In conclusion, Pentecostals consider the narrative of Jephthah's vows to be an ambition that takes its toll, a picture of a man who failed to carry out his fatherly function, a warning to be careful in his words, and a useless story of regret.Seorang ayah semesti mendidik, melindungi, mengayomi, memberikan rasa aman dan nyaman kepada anak-anaknya. Namun, apa yang Alkitab ceritakan terkait narasi nazar Yefta tidaklah menunjukan hal yang demikian. Karena dampak dari nazar itu, akhirnya Yefta harus mempersembahkan putri semata wayangnya sebagai korban bakaran untuk Allah. Padahal, Allah melalui yang digambarkan Alkitab tidaklah pernah menginginkan korban bakarannya adalah seorang manusia. Artikel ini berupaya membaca narasi nazar Yefta dari cara pandang kaum Pentakostal. Pengunaan metode kualitatif naratif dan mengelaborasikannya dengan kajian literatur diharapkan sanggup memberikan tilikan yang mendalam tentang kehidupan Yefta, memberikan gambaran yang kuat terkait narasi nazar Yefta dalam Hakim-hakim 11: 29-40, dan cara kaum Pentakostal memandang nazar ini. Disimpulkan, kaum Pentakostal menilai narasi nazar Yefta ini merupakan ambisi yang memakan korban, gambaran seorang pria yang gagal menjalankan fungsi keayahan, sebagai peringatan untuk berhati-hati dalam perkataan, dan kisah penyesalan yang tidak berguna.